Classification of Costs and Their Impact on the Performance of Agricultural Enterprises - Valynkevych, N. V.; KobylynskyiV. М. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The article is focused on the analysis of costs involved in agricultural production, by case of agricultural enterprises located in Zhytomyr region (Ukraine). This objective is justified by the essential impact of costs on the enterprise performance, being a factor of output and pricing, financial condition, competitiveness of product groups and the whole enterprise, profit etc. Specifics of the agricultural production and their implications for production costs in this sector are highlighted. The statistical analysis on agricultural enterprises of Zhytomyr region in 2015 and 2016 includes the official data on the overall agricultural performance; distribution of the operation results by agricultural products and agricultural services; distribution of operation results by plant growing and animal husbandry. The data are collected on the basis of annual statistical observation, by filling the form “Main economic indicators of the operation of agricultural enterprises”. The analysis shows that more than 97% of the total income in 2015–2016 was generated by agricultural products, with only 3% of the income earned by rendering agricultural services. The year of 2016 marked the upward tendency in both production and total costs (6.7% and 8%, respectively), in parallel with 7 percent decrease in the net income, which, in effect, reduced the profitability rate by 0.4%. According to the statistical observation data, in 2015 and 2016 a lion share of income from agricultural business was earned by the surveyed agricultural enterprises of Zhytomyr region from plant-growing: 97.8% in 2015 and 99.4% in 2016. These data show a marginal role of animal husbandry in the agricultural business and its imbalanced operation in the region under study. The profitability rate in plant-growing increased in 2015– 2016 (40% and 41.3%, respectively), but it fell in animal husbandry from 5.2% to 1.1%, which was approaching to the zero net revenue.